2022
DOI: 10.1007/s11356-021-17119-9
|View full text |Cite
|
Sign up to set email alerts
|

Can environmental tax bring strong porter effect? Evidence from Chinese listed companies

Abstract: Existing researches verify Porter hypothesis mainly through one of its core establishment paths, innovation compensation, but ignore the other one, rst-mover advantage. To further clarify the mechanism of Porter hypothesis, this paper considers both paths and further distinguishes between environmental R&D and nonenvironmental R&D. Based on the principle of the smooth transition of "charge to tax" in China, this paper, taking Chinese A-share listed companies that have disclosed environmental R&D from 2008 to 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
(12 reference statements)
2
16
0
Order By: Relevance
“…In other words, both carbon performance and technological innovation are driving factors of corporate financial performance. The finding of the impact of technological innovation on financial performance is consistent with most researchers as discussed in the literature review ( Yeguang and Bo, 2018 ; Tariq et al, 2019 ; Yuan and Guangpei, 2021 ; Lei et al, 2022 ). But only few studies focus on empirical research on the relation between carbon performance and financial performance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In other words, both carbon performance and technological innovation are driving factors of corporate financial performance. The finding of the impact of technological innovation on financial performance is consistent with most researchers as discussed in the literature review ( Yeguang and Bo, 2018 ; Tariq et al, 2019 ; Yuan and Guangpei, 2021 ; Lei et al, 2022 ). But only few studies focus on empirical research on the relation between carbon performance and financial performance.…”
Section: Discussionsupporting
confidence: 89%
“…From the perspective of sustainable development of enterprises, the resource-based view doctrine proposes that technological innovation in enterprises is one of the most precious resources that can improve the core competitiveness and can bring differentiation of products or services, such as lower cost, higher quality or enable enterprises to gain competitive advantage in the market, and ultimately enhance enterprise value. At the same time, technological innovation brings unique resources to firms, which are often heterogeneous and difficult to replicate among firms, providing an irreplaceable advantage for firms’ competition ( Yuan and Guangpei, 2021 ; Lei et al, 2022 ). According to the signaling theory, investors have more confidence and higher expected value for the future operation of enterprises with large investment in technological innovation.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…The essence and experience of applying environmental taxation are considered in the works of Lei et al (2022), Liu et al (2022), Matti et al (2022), Zhao et al (2022). But the contribution of environmental taxation to the sustainable development of the ecological economy has not been sufficiently studied and defined, which is a gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the "innovation compensation" effect of environmental regulations offsets the cost of environmental regulation compliance (Qiu et al, 2018) and increases enterprise productivity and performance (Hamamoto, 2006). In addition, when the green technologies mastered by these enterprises are mature, they will also have a first-mover advantage (Lei et al, 2022). The market competitiveness of technologically upgraded enterprises will be further strengthened in the future, resulting in the growth of enterprise economic benefits.…”
Section: Environmental Tax Revenue and Enterprise Economic Growthmentioning
confidence: 99%
“…Previous studies have assessed the potential for beneficial effects of environmental taxes on economic growth and technological innovation input in China, with some scholars proposing positive benefits and others suggesting no or even negative benefits. First, Lei et al (2022), Abdullah andMorley, 2014, andWalid Oueslati, (2014) reported a causal relationship between environmental tax and enterprise performance. Early studies suggested a positive relationship between environmental tax and economic growth.…”
Section: Introductionmentioning
confidence: 99%